Biosorption of Pb(II) From Aqueous Solutions by a Fungal Biomass in a Batch System: Equilibrium and Kinetic Studies - Tunali, Yagmur; Karaca, Hulya; Tay, Turgay; Kivan, Merih; Bayramoglu, Glay (Asian Journal of Chemistry, 2010)
In this study, the biosorption capacity of the fungus Sporotricum sp. biomass in removing of Pb(II) ions from aqueous solution were investigated with different parameters, such as pH, temperature and initial metal ion concentrations in a batch adsorption system. The maximum biosorption of Pb(II) ions onto the Sporotricum sp. biomass was 15.48 mg per g of the biomass. The biosorption of Pb(II) ions increased with increased pH up to 6.0 at which the maximum biosorption was obtained. Temperature change between 15 and 40 ºC did not affect the biosorption capacity of the fungal biomass. Desorption of the Pb(II) ions was achieved using 0.1 M HCl solution. Biosorption equilibria were established in about 24 h. Biosorption experimental data could be well interpreted by the Langmuir model with maximum adsorption capacity of 16.42 mg g-1 of Pb(II) ion on to the Sporotricum sp. biomass. Also the correlation regression coefficients show that the biosorption process can be well-defined by Freundlich model. The change in biosorption capacity with time was found to fit the pseudo-second-order kinetic model.